Cardiology career satisfaction: a little academic activity goes a long way - deFilippi, Christopher R. (Frontiers in Cardiovascular Medicine, 2024)
The professional landscape for clinical cardiologists and most physicians has changed dramatically in the last decade in the United States. By the end of 2020, 87% of cardiologists were integrated with a health system (employed or part of a professional services agreement). Physicians transitioning to a large employer are often dissatisfied with the lack of autonomy and the pressure from “one-size-fits-all” productivity targets. The results from physician surveys indicate that physicians practicing clinically in an academic environment have greater job satisfaction. Potentially even a modest amount of time comprising 10-20% of total effort spent on academic pursuits that are most meaningful to the individual physician can result in nearly a two-thirds lower risk of burnout compared with physicians who don't receive this time. The opportunity to participate in this special topic compendium by cardiovascular specialists at one regional integrated health system in the United States is an example of an opportunity to successfully incorporate meaningful professional academic opportunities into a clinical care environment.